BENEFITS OF LEARNING MEDIA IN THE LEARNING AND TEACHING PROCESS AT UNIVERSITY - Fatma Cetinkaya; Khairuna Khairuna; Kamil Arif KÄ±rkÄ±c (Universitas Labuhanbatu, 2023)
The goal of this study was to learn about the benefits of employing media in the learning and teaching process for university students. The descriptive approach and qualitative research were employed in this study. According to the findings of this study, employing media in the learning and teaching process for university students is quite beneficial. The medium relayed information from the source (lecturer) to the recipient (student). Media in the learning and teaching process might be used as a message deliverer technology (information) or a physical tool to deliver learning content. According to the findings of this study, the benefits of media include facilitating contact between lecturers and students and assisting students in learning more effectively.Keywords: Learning Media and the Learning Process